Efektivitas Penggunaan Media Pembelajaran Visual untuk Mengatasi Kesulitan Membaca Siswa Kelas IV Sekolah Dasar Negeri 06966 Kota Medan - Dedek Ahmad; Ahmad Calam; Syahrina Anisa Pulungan (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
Reading ability is a fundamental literacy skill that plays a crucial role in elementary students’ academic development. Nevertheless, many students continue to experience difficulties in reading fluency, reading speed, and reading comprehension, which may hinder their overall learning achievement. This study investigates the effectiveness of visual learning media in overcoming reading difficulties among 14 fourth-grade students at SD Negeri 060966 Medan City. A qualitative descriptive approach was employed, involving 14 students, one classroom teacher, and one school principal as research participants. Data were collected through classroom observations, semi-structured interviews, and documentation and were analyzed using the Miles, Huberman, and Saldana interactive model with the support of NVIVO 15 software. The findings indicate that visual learning media significantly enhanced students’ reading comprehension, motivation, concentration, and classroom engagement. Of the 14 students observed, 11 demonstrated noticeable improvement in understanding textual content after learning activities incorporated pictures and illustrations. Visual representations enabled students to interpret reading materials more concretely and meaningfully. However, limited digital facilities and insufficient technological competencies among teachers remained challenges to the optimal implementation of visual learning media. These findings highlight the practical value of integrating visual resources into elementary literacy instruction to support students experiencing reading difficulties.